1979
DOI: 10.1139/p79-211
|View full text |Cite
|
Sign up to set email alerts
|

New trapped-electron and trapped-hole centres in X-rayed KCl:Tl+ crystals

Abstract: The optical absorption spectra of KC1 crystals containing TI+ ions have been investigated. After X-ray irradiation at 300 K two absorption bands are observed at 228 and 280 nm at 77 K whichdo not arise from the same centres. A correlation among the 228 nm. 280 nm. and F bands is found during the optical or thermal excitation of the X-rayed crystals. The 228 nm band is assigned to a trapped-hole centre, namely V2 centre closely associated with TIt. while the 280 nrn hand is assigned to a trapped-electron centre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
2

Year Published

1981
1981
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 5 publications
(5 reference statements)
0
1
2
Order By: Relevance
“…Absorption bands at 640 and 380 nm due to Tl 0 [11] are not observed in the present study. Therefore it is suggested that not Tl 0 but Tl À is created by the electrolytic coloration.…”
Section: Resultscontrasting
confidence: 79%
See 1 more Smart Citation
“…Absorption bands at 640 and 380 nm due to Tl 0 [11] are not observed in the present study. Therefore it is suggested that not Tl 0 but Tl À is created by the electrolytic coloration.…”
Section: Resultscontrasting
confidence: 79%
“…Tl 0 is created by trapping of electron at Tl + under X-ray irradiation at 77 K, but it is not stable at 290 K [10,11]. Absorption bands at 640 and 380 nm due to Tl 0 [11] are not observed in the present study.…”
Section: Resultscontrasting
confidence: 64%
“…The methods for obtaining such negative metal ions were various, starting with X-ray irradiation, additive or electrolytic coloration. So far, was demonstrated the existence of Pb - [2], Ag - [3], Cu - [4], Tl - [5] and even Sn - [6]. The change of the valence for heavy metal ions were also observed in CaF 2 : Pb 2+ crystals under X-ray irradiation at the temperatures over 300 K, where Pb 2+ ions are transformed into Pb + , Pb + -Pb 2+ and/or Pb 0 (2) centres [7].…”
mentioning
confidence: 97%